Strengthening the Bachelor of Library and Information Science curriculum in the Philippines - Irinco, Reina R.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study, in view of the changing information environment in the Philippines, attempted to determine the effect of Republic Act 6966 (law that allows Bachelor of Science in Education (BSE), Bachelor of Elementary Education (BEED), and Bachelor of Secondary Education (BSEd) majoring in library science to take the licensure examination for librarians) and the possible ways of revitalizing the library and information science programs that are currently offered in the nine colleges and universities in Metro Manila.
This research used an interview schedule as a means to gather the data. Fifteen (15) out of the twenty-two (22) respondents agreed to be interviewed, mostly librarians, library administrators and deans. The study discussed the nine colleges and universities namely Centro Escolar University (CEU), Manuel Luis Quezon University (MLQU), National Teachers College (NTC), Philippine Normal University (PNU), Philippine Women's University (PWU), Polytechnic University of the Philippines (PUP), University of Manila (UM), University of Santo Thomas (UST) and University of the East (UE) where the respondents stated their insights and opinions regarding the effect of RA 6966 on library programs. Questions focused particularly on whether their respective library schools can separate from their Colleges of Education, the reasons as to whether they can or cannot separate from them, the advantages and disadvantages of separating from them, and their ideas and suggestions for revitalizing the LIS program.
The findings show that most private colleges/ universities cannot separate from their colleges of education due to dwindling enrollees, faculty, facilities and financial reasons. There are some advantages once separated from the college of education, such as more focus on content and approach in librarianship. Standardization of the curricula is timely and necessary. Organizations such as the Philippine Association of Teachers in Library Science (PATLS) must see to it the curriculum meets certain requirements imposed on the colleges and universities. In addition, instead of staying with the College of Education in their universities, library and information science as a program should look for ways to transfer to other suitable colleges in order to be able to focus more on what is required of the profession by the nation.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library education -- Philippines; Library schools -- Curricula. -- Philippines